2007
DOI: 10.1007/s00384-007-0342-7
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor beta-1 in rectal tumour, mucosa and plasma in relation to radiotherapy and clinical outcome in rectal cancer patients

Abstract: Higher levels of total TGF-beta1 in tumour tissue at surgery may be indicative of distant metastases, and low levels of active TGF-beta1 in plasma may indicate a risk of developing secondary metastases. Lower levels of total TGF-beta1 in rectal mucosa may influence risk of local recurrence. Measurement of TGF-beta1 in rectal cancer patients may be of clinical use in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 24 publications
2
13
0
Order By: Relevance
“…Our explanation is that these high levels of total TGF-β1 give the tumor an opportunity to exert a localized suppression of the immune system and thus facilitate tumor spread. Our findings are somewhat similar to those of Friedman et al and Angenete et al (12,13), who showed a correlation between TGF-β1 and disease progression. In resected patients, TGF-β1 could work as a tumor suppressor.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our explanation is that these high levels of total TGF-β1 give the tumor an opportunity to exert a localized suppression of the immune system and thus facilitate tumor spread. Our findings are somewhat similar to those of Friedman et al and Angenete et al (12,13), who showed a correlation between TGF-β1 and disease progression. In resected patients, TGF-β1 could work as a tumor suppressor.…”
Section: Discussionsupporting
confidence: 82%
“…However, TGF-β1 only seems to be a tumor suppressor in the early stages of the cancer; with increasing tumor load, TGF-β1 promotes tumor progression. It has been shown that TGF-β1 in specimens of colorectal cancer is associated with a poor prognosis and an increased risk of recurrence and tumor progression (12,13). The levels of both total and active TGF-β1 have also been found to be higher in patients with colorectal cancer, and they have also been associated with disease progression (14).…”
Section: Introductionmentioning
confidence: 99%
“…A previous investigation from our group in fact showed that RT and surgery induced depression of TGFβ in rats in the first postoperative week followed by up-regulation in the late period (38,40). Similarly, other authors showed lower levels of active TGFβ in both tumour tissue and rectal mucosa in patients irradiated for rectal cancer (38). Evidence points towards RT-induced activation of latent TGFβ but this activation may only be seen in a limited time window, which may not have been captured in these studies.…”
Section: Discussionmentioning
confidence: 77%
“…TGFβ participates in the remodelling of the ECM, but has many other functions, such as suppression of the immune system and regulation of cell growth. It was also shown to act both as an inhibitor of tumour growth and as a promoter of tumour progression (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, the TGF-β plasma concentration has been reported to increase in a wide variety of advanced stages of human cancer, such as esophageal (5), gastric (6), colorectal (7)(8)(9)(10), hepatocellular (11)(12)(13)(14)(15)(16)(17), lung (18)(19)(20) and breast cancer (21)(22)(23)(24)(25)(26)(27)(28). These findings suggest that systemic elevation of TGF-β may be involved in tumor progression.…”
Section: Introductionmentioning
confidence: 99%